ANALISIS PELAKSANAAN PEMOTONGAN, PENYETORAN PAJAK PENGHASILAN PASAL 21 ATAS PEGAWAI TETAP PADA DINAS PENDAPATAN DAERAH KABUPATEN KUTAI BARAT - Imam Nazarudin Latif, Suhaiti, LCA. Robin Jonathan, (EKONOMIA, 2016)
The research problems is whether the calculation of income tax article 21, Department of Revenue West Kutai are in accordance with the Tax Act 36 of 2008.The aim of this study was to investagate compliance with Department of Revenue West Kutai in the Implementation of Cutting, Payment of Income Tax on Employees according to Article 21 of the Tax Law in force. Basic theory used is the theory of accounting, tax accounting, tax theory, and income tax.The hypothesis is used in calculating the income tax article 21 on permanent employee Department of Revenue West Kutai. The analytical tool used to test the truth of the hypothesis is: 1. By using Procedure of the General Taxation and No. 36 Year 2008 on Income Tax. 2. Calculation of Income Tax Article 21, Deposit SSP, Recap payroll in 2014 and reporting SPT.Based on the results of the study authors obtained results of the analysis that cuts, remittance of income tax under Article 21 of the permanent employee Department of Revenue West Kutai, in contrast to the cuts, remittance of income tax under Article 21 of the permanent employee under the Act applies.From the results of analysis and discussion above it can be concluded that the cuts, remittance of income tax under Article 21 of the permanent employee Department of Revenue West Kutai, has not been fully adhered to and applied in accordance with the tax laws that apply so that the hypothesis can be accepted